1990
DOI: 10.1136/gut.31.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adhesion and disease activity in Helicobacter associated chronic gastritis.

Abstract: Ultrastructural examination of biopsies showing Helicobacter pylon associated chronic gastritis reveals close attachment between gastric surface epithelial celis and the organism. The finding of 'adhesion pedestals', which represents a cellular response to the presence of the organism, is analogous to the response ofintestinal cells to enteropathogenic E coli. Thus the development of bacterial attachment sites in H pylori associated gastritis might be an indication of pathogenicity. We have therefore explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
190
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(197 citation statements)
references
References 22 publications
(1 reference statement)
4
190
0
3
Order By: Relevance
“…In the human stomach, H. pylori was first described to adhere to the apical surface of the surface mucous cells, 20 and its ability to adhere was considered an essential factor for the stable infection by H. pylori. 21 In addition, several studies using in vitro experimental systems have suggested that this attachment accelerates the production of interleukin-8, which induces neutrophil infiltration. 22,23 In the human stomach, as shown by Shimizu et al, 24 this organism actively col-onizes not only the apical surface but also the SMGL.…”
Section: Discussionmentioning
confidence: 99%
“…In the human stomach, H. pylori was first described to adhere to the apical surface of the surface mucous cells, 20 and its ability to adhere was considered an essential factor for the stable infection by H. pylori. 21 In addition, several studies using in vitro experimental systems have suggested that this attachment accelerates the production of interleukin-8, which induces neutrophil infiltration. 22,23 In the human stomach, as shown by Shimizu et al, 24 this organism actively col-onizes not only the apical surface but also the SMGL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the presence of different cell adherence forms of H. pylori has been correlated with cytolysis and disintegration/destruction of the gastric epithelium (3,11,13). Another feasible indirect mechanism of action is the recruitment and activation of inflammatory cascade(s) with potent chemokines (15).…”
Section: Discussionmentioning
confidence: 99%
“…This was comparable to, but possibly biochemically different from, the ''attaching-effacing'' effect observed with E. coli strains carrying the eae-gene (EPEC-strains; 12,17). The specialised attachment sites on gastric cells were described as ''abutting'' (3,10), ''pedestal'' (8,11,12,24), or ''cup-like'' (8). However, some investigators failed to show such pedestal formations (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations